The Thoughts of Syeid Muhammad Naquib Al-Attas; Adab as a Foundation - Ismarani Junia Putri; Izzatuzzahroh Izzatuzzahroh; Muhammad Sirozi (Journal of Educational Sciences, 2026)
This study examines the perspectives of Muslim thinkers outside Southeast Asia on the concept of education, its implementation within educational systems, and its strengths and limitations in contemporary contexts. The thought of Syed Muhammad Naquib al-Attas is used as the main focus due to his significant contribution to the discourse on Islamic education and the Islamization of knowledge. The research aims to explore the philosophical foundations of Al-Attas’s educational ideas and evaluate their relevance to modern educational challenges. This research employs a literature study using a descriptive qualitative approach by analyzing primary works of Al-Attas and related scholarly discussions. The findings show that Al-Attas emphasizes adab as the central goal of education, which refers to the cultivation of proper moral conduct and the correct placement of knowledge and human beings within the order of existence. His concept of education also stresses the integration of knowledge within the framework of Tawhid, rejecting the dichotomy between religious and secular sciences and criticizing the secularization of knowledge. However, his ideas have also been criticized, particularly by secular-liberal scholars who consider the Islamization of knowledge difficult to implement in the modern academic environment. Despite these debates, Al-Attas’s thought offers an important philosophical foundation for the development of contemporary Islamic education.